Penumbangan Rezim melalui Gerakan Masyarakat Dunia Maya (Media Sosial) di Timur Tengah - Taufik Taufik (Indonesian Association for International Relations, 2018)
Social media has become a new alternative in the field of communication in the circle of people's lives in the Middle East which offers freedom especially in terms of self-expression, something that has been hindered by the censorship of anti-critic dictatorial regimes. Unpredictably, the expression of disappointment expressed by Middle Eastern society towards the government through social media can be a lighter revolution that hit the Middle East countries in 2011. The purpose of this research is to know, explore, and describe some of the links between the revolution, the public sphere, and the movement of society through social media in the Middle East. A revolution in Tunisia in 2011 has been a generator of community movements in overthrowing the muscle rigid regimes in some Middle Eastern countries such as Egypt and Libya.